2017
DOI: 10.1111/jcmm.13401
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular aggregation of aquaporin‐4 is different in muscle and brain: correlation with tissue susceptibility in neuromyelitis optica

Abstract: Neuromyelitis optica (NMO) is an autoimmune demyelinating disease of the central nervous system (CNS) caused by autoantibodies (NMO‐IgG) against the water channel aquaporin‐4 (AQP4). Though AQP4 is also expressed outside the CNS, for example in skeletal muscle, patients with NMO generally do not show clinical/diagnostic evidence of skeletal muscle damage. Here, we have evaluated whether AQP4 supramolecular organization is at the basis of the different tissue susceptibility. Using immunofluorescence we found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 45 publications
0
16
0
1
Order By: Relevance
“…In the light of this, the data in Figure 1 of Rosito et al [1] showing minimal or non-specific AQP4-IgG binding to skeletal muscle in seropositive NMO are perplexing, as other studies have shown that systemically administered AQP4-IgG rapidly binds to rodent skeletal muscle [8] and that IgG binding is found on skeletal muscle in humans with NMO myositis [9]. One potential explanation for this discrepancy might be loss of AQP4 antigenicity for autoantibody binding in the non-fixed frozen muscle used by Rosito et al [1].If AQP4 cluster size does not account for sparing of skeletal muscle in NMO, then what does? One possibility is complement inhibitor protein CD59, which is strongly expressed in skeletal muscle and other AQP4-expressing tissues in the periphery such as kidney and stomach.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…In the light of this, the data in Figure 1 of Rosito et al [1] showing minimal or non-specific AQP4-IgG binding to skeletal muscle in seropositive NMO are perplexing, as other studies have shown that systemically administered AQP4-IgG rapidly binds to rodent skeletal muscle [8] and that IgG binding is found on skeletal muscle in humans with NMO myositis [9]. One potential explanation for this discrepancy might be loss of AQP4 antigenicity for autoantibody binding in the non-fixed frozen muscle used by Rosito et al [1].If AQP4 cluster size does not account for sparing of skeletal muscle in NMO, then what does? One possibility is complement inhibitor protein CD59, which is strongly expressed in skeletal muscle and other AQP4-expressing tissues in the periphery such as kidney and stomach.…”
mentioning
confidence: 93%
“…Rosito et al [1] report evidence that differences in the supramolecular organization of AQP4 in skeletal muscle versus brain astrocytes are responsible for the sparing of skeletal muscle in NMO, arguing that the size of AQP4 supramolecular clusters (called orthogonal arrays of particles, OAPs) is smaller in skeletal muscle than in astrocytes resulting in reduced AQP4-IgG binding. This mechanism is motivated by the observation that some AQP4-IgG autoantibodies bind better to AQP4 OAPs than to separated AQP4 tetramers [2] and that AQP4 OAPs are required for C1q binding and complement activation [3].…”
mentioning
confidence: 99%
“…The use of g‐STED super‐resolution microscopy versus freeze‐fracture electron microscopy (FFEM) to analyse skeletal muscle and brain AQP4 supramolecular assemblies (OAPs) used in our study 1 has been disputed by Verkman et al . While we agree that FFEM is the gold standard to visualise OAPs and also measure their size, we also are aware that the very small amount of the plasma membrane that can be suitable for analysis represents a major limit to obtaining statistically significant data (such as the OAP dimension) representative of the entire tissue.…”
mentioning
confidence: 99%
“…
We would like to thank you for the opportunity to respond to the questions raised in Dr Verkman's letter and to elucidate related aspects. We also thank Dr Verkman and colleagues for their attention to our study.The use of g-STED super-resolution microscopy versus freezefracture electron microscopy (FFEM) to analyse skeletal muscle and brain AQP4 supramolecular assemblies (OAPs) used in our study [1] has been disputed by Verkman et al While we agree that FFEM is the gold standard to visualise OAPs and also measure their size, we also are aware that the very small amount of the plasma membrane that can be suitable for analysis represents a major limit to obtaining statistically significant data (such as the OAP dimension) representative of the entire tissue. In contrast, STED microscopy has the enormous advantage of analysing, in real time, very large portions of the plasma membrane, with a resolution that in our setup can reach approximately 30 nm, providing the possibility to have a more complete vision of the entire tissue and handle a large amount of data.Considering the 'contradiction of available data', Verkman et al refer to an FFEM study on OAP structure and organisation performed before the identification of AQP4 (or MIWC) as the molecular determinant of OAPs [2].
…”
mentioning
confidence: 99%
See 1 more Smart Citation